Bovine Tuberculosis: Prevalence and risk factor assessment in cattle and cattle owners in Wuchale-Jida District, central Ethiopia - Ameni, G.; Amenu, K.; Tibbo, Markos (2003)
A cross-sectional study was conducted between December 2001 and April 2002 on 94 households and 763 (188 indigenous and 575 crossbred) cattle to determine the prevalence of bovine tuberculosis (BTB) and assess its public health implications in smallholder farms in Wuchale-Jida District, Central Ethiopia. Cluster sampling, single intradermal tuberculin (SIDT) and comparative intradermal tuberculin (CIDT) tests, a questionnaire, and mycobacteriology were used. Based on the CIDT test, herd and individual animal prevalences of BTB were 42.6% and 7.9%, respectively. The individual animal prevalence was significantly affected by herd size (P<0.01), age (P<0.0001) and body condition (P<0.05). Among the interviewed households, 24.5% (23 of 94) had experienced at least one human tuberculosis case in the family. Of these families, 43.5% (10 of 23) had reactor cattle. Nevertheless, no statistically significant association (P>0.05) was observed between reactor cattle and human tuberculosis cases in households. The habit of milk and meat consumption was affected by occupation (P<0.0001) and location of household residence (P<0.001). Although the level of education influenced the habit of milk consumption (P<0.05), it did not impact the habit of meat consumption (P>0.05). Less than half (38.3%; 36 of 94) of the respondents knew about BTB, and only 30.8% (29/94) of the respondents were conscious of its transmission from cattle to humans. Secondary data analysis from Muka-Turri clinic indicated that 85.6% of the human tuberculosis cases were from rural parts of the district. Although the BTB prevalence seems low, its potential risk to public health was important based on food consumption, poor sanitary measures, and the lack of understanding about its zoonosis.